The Influence of Water-Unextractable Arabinoxylan and Its Hydrolysates on the Aggregation and Structure of Gluten Proteins - Sun, Juan; Si, Xiaojing; Li, Tingting; Zhao, Jiajia; Qian, Haifeng; Li, Yan; Zhang, Hui; Qi, Xiguang; Wang, Li (Frontiers in Nutrition, 2022)
This study aimed to investigate the influence of water-unextracted arabinoxylan (WUAX) and its hydrolysates on the aggregation and structure of gluten proteins and reveal the underlying mechanism. In this work, the WUAX was treated with enzymatic hydrolysis and the changes of their molecular weights and structures were analyzed. Meanwhile, the conformation and aggregation of gluten were determined by reversed-phase HPLC, FT-Raman spectroscopy, and confocal laser scanning microscopy. The results showed that the extra WUAX could impair the formation of high Mw glutenin subunits, and the enzymatic hydrolysis arabinoxylan (EAX) could induce the aggregation of gluten subunits. And, the gluten microstructure was destroyed by WUAX and improved by EAX. Besides, the interactions of WUAX and EAX with gluten molecules were different. In summary, these results indicated that enzymatic hydrolysis changed the physicochemical properties of arabinoxylan and affected the interaction between arabinoxylan and gluten proteins.